(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper delves into the radical transformation the information economy is undergoing, moving from traditional leadership models to an era of digital leadership, in a volatile and rapidly evolving business landscape driven by algorithms, programs, and codes designed to track user activity across digital platforms. In this chaotic environment, organizations are no longer bound by a singular path to leadership success to outpace competitors. Historically, nations fortified their economies by hoarding gold and precious metals; later, the discovery and rising global demand for oil shifted the focus to stockpiling petroleum reserves, as seen in the prosperity of Saudi Arabia, the UAE, Iraq, and other OPEC nations, whose economies are predominantly oil dependent. Today, the critical economic driver is technology, marking not merely the so-called "digital age" but what I term the "age of algorithms." In this algorithmic era, organizations meticulously track user behaviour across the web, mining browsing patterns, preferences, and dislikes. These data are harnessed by digital leaders to devise strategies, while the brightest minds in technology empower organizational leadership with insights to inundate users with tailored choices. The future of leadership will become increasingly customized, integrating cutting-edge technology with leadership strategy into a cohesive, sophisticated framework. This paper proposes a novel leadership model—the "coded model"—in which leadership becomes ever more personalized, driven by the algorithms that monitor and interpret user movements and behaviours online.